2017
DOI: 10.3390/land6040068
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Research on the Ecology and Management of the ‘Wulo’ Monsoon Rainforest in Wunambal Gaambera Country, North Kimberley, Australia

Abstract: Indigenous groups are increasingly combining traditional ecological knowledge and Western scientific approaches to inform the management of their lands. We report the outcomes of a collaborative research project focused on key ecological questions associated with monsoon vine thickets in Wunambal Gaambera country (Kimberley region, Western Australia). The study mapped monsoon rainforests and analysed the environmental correlates of their current distribution, as well as the historical drivers of patch dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…This study synthesized environmental information, historical datasets, and remote sensing imagery to evaluate the effectiveness of reinstating Aboriginal fire regimes on the current distribution and patch dynamics of the monsoon rainforests. As would be expected, [16] identified that the rainforests would expand into patches when fires occurred with low frequency and cattle were not present. However, [16] noted that in high-frequency fire regimes with cattle present, the rainforest did not produce more patches, but rather the understory would be suppressed through trampling and fine-scale fuel consumption.…”
Section: Highlightssupporting
confidence: 54%
See 3 more Smart Citations
“…This study synthesized environmental information, historical datasets, and remote sensing imagery to evaluate the effectiveness of reinstating Aboriginal fire regimes on the current distribution and patch dynamics of the monsoon rainforests. As would be expected, [16] identified that the rainforests would expand into patches when fires occurred with low frequency and cattle were not present. However, [16] noted that in high-frequency fire regimes with cattle present, the rainforest did not produce more patches, but rather the understory would be suppressed through trampling and fine-scale fuel consumption.…”
Section: Highlightssupporting
confidence: 54%
“…Three of the papers in this Special Issue deal with stand heterogeneity and patches. In [16], the long-term persistence of patches in monsoon rainforests of Western Australia and the role of Aboriginal burning practices in sustaining them were evaluated. In [5], the characteristics surrounding unburned islands and peninsulas were discussed.…”
Section: Highlightsmentioning
confidence: 99%
See 2 more Smart Citations
“…A high proportion of these errant bioregions fall under the denomination of traditional indigenous uses (e.g., Central Arnhem = 98%, MacDonnell Ranges = 48%, and Tiwi Cobourg = 72%). While not officially listed under the category nature conservation, these areas are often managed for conservation by local Aboriginal groups, based on traditional ecological knowledge (Yibarbuk et al 2001, Vigilante et al 2017) and as such are not likely to be at high risk of being degraded by future anthropogenic development.…”
Section: Discussionmentioning
confidence: 99%